Universal coarsening in a homogeneous two-dimensional Bose gas - Gazo, Martin; Karailiev, Andrey; Satoor, Tanish; Eigen, Christoph; Galka, Maciej; Hadzibabic, Zoran (Science, 2025)
Coarsening of an isolated far-from-equilibrium quantum system is a paradigmatic many-body phenomenon, relevant from subnuclear to cosmological length scales and predicted to feature universal dynamic scaling. Here, we observed universal scaling in the coarsening of a homogeneous two-dimensional Bose gas, with exponents that match analytical predictions. For different initial states, we reveal universal scaling in the experimentally accessible finite-time dynamics by elucidating and accounting for the initial-state-dependent prescaling effects. The methods we introduce allow direct comparison between cold-atom experiments and nonequilibrium field theory and are applicable to any study of universality far from equilibrium.